Risk of enzyme allergy in the detergent industry. Issue 2 (1st February 2000) - Vanhanen, Markku; Tuomi, Timo; Tiikkainen, Ulla; Tupasela, Outi; Voutilainen, Risto; Nordman, Henrik
Abstract : OBJECTIVES: To assess the prevalence of enzyme sensitisation in the detergent industry. METHODS: A cross sectional study was conducted in a detergent factory. Sensitisation to enzymes was examined by skin prick and radioallergosorbent (RAST) tests. 76 Workers were tested; 40 in manufacturing, packing, and maintenance, and 36 non-exposed people in management and sales departments. The workers were interviewed for work related respiratory and skin symptoms. Total dust concentrations were measured by a gravimetric method, and the concentration of protease in air by a catalytic method. RESULTS: Nine workers (22%) were sensitised to enzymes in the exposed group of 40, whereas none were sensitised in the non-exposed group. All the sensitised people had symptoms at work; all had rhinitis and one had asthma. Protease concentrations were generally <20 ng/m 3, but occasional peak values up to 80 ng/m 3 were detected in the packing and maintenance tasks, and high values of >1 μg/m 3 in the mixing area. CONCLUSION: Despite the use of encapsulated enzyme preparations, high enzyme concentrations in workplace air are possible, resulting in a higher risk of sensitisation than expected.